Akibat Hukum yang Timbul dari Perkawinan Pengungsi Rohingya dan Warga Negara Indonesia: Studi Kasus Kota Medan - dwi pranata (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study is motivated by the practice of mixed marriages between Rohingya refugees and Indonesian citizens, which raises legal issues, particularly regarding marital status and children’s rights. The study aims to analyze the legal consequences of such marriages. It employs a normative-empirical legal method with a descriptive qualitative approach through observation, interviews, and documentation. The findings indicate that these marriages cannot be officially registered due to administrative constraints and are therefore only recognized religiously. As a result, children face difficulties in obtaining birth certificates and are at risk of becoming stateless. It is concluded that affirmative policies and inclusive regulations are needed to ensure effective legal protection.